European security the roles of regional organisations - Møller, Bjørn (Routledge, 2012)
This comprehensive book offers a theoretically founded and thoroughly documented analysis of European security, with a special emphasis on the role played by the United Nations and the various regional and sub-regional organisations, especially the North Atlantic Treaty Organisation, the Organisation for Security and Cooperation in Europe, the Council of Europe and the European Union. It will be required reading for all students and scholars of European security and the organisations which underpin it.